2016
DOI: 10.1038/srep36122
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evidence of RNA polymerase II gene reveals the origin of worldwide cultivated barley

Abstract: The origin and domestication of cultivated barley have long been under debate. A population-based resequencing and phylogenetic analysis of the single copy of RPB2 gene was used to address barley domestication, to explore genetic differentiation of barley populations on the worldwide scale, and to understand gene-pool exchanges during the spread and subsequent development of barley cultivation. Our results revealed significant genetic differentiation among three geographically distinct wild barley populations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 82 publications
1
5
0
Order By: Relevance
“…Functionally, RPB2 gene is responsible for the transcription of protein-encoding genes (Sawadogo and Sentenac, 1990) and present as single-copy in all eukaryotes (Thuriaux and Sentenac, 1992). A high level of polymorphisms in this gene makes this an excellent tool to study molecular evolution and phylogenetic relationships (Matheny et al, 2007; Krimitzas et al, 2013; Wang et al, 2016; Kruse et al, 2017). Stockinger et al (2014) reported RPB2 gene as a potential marker for adequate phylogenetic resolution to resolve fungal lineages when compared to rDNA loci.…”
Section: Introductionmentioning
confidence: 99%
“…Functionally, RPB2 gene is responsible for the transcription of protein-encoding genes (Sawadogo and Sentenac, 1990) and present as single-copy in all eukaryotes (Thuriaux and Sentenac, 1992). A high level of polymorphisms in this gene makes this an excellent tool to study molecular evolution and phylogenetic relationships (Matheny et al, 2007; Krimitzas et al, 2013; Wang et al, 2016; Kruse et al, 2017). Stockinger et al (2014) reported RPB2 gene as a potential marker for adequate phylogenetic resolution to resolve fungal lineages when compared to rDNA loci.…”
Section: Introductionmentioning
confidence: 99%
“…According to molecular evidence, however, barley seems to have been domesticated more than once, with independent origins in the Fertile Crescent and in Central Asia (Morrell & Clegg 2007). Additional origins have been suggested in Morocco (Igartua et al 2013) and on the East Asian Tibetan Plateau (Wang et al 2016). As barley can withstand many different climatic and soil conditions, it subsequently spread over vast areas and became a principal dietary grain.…”
Section: Introductionmentioning
confidence: 99%
“…Genome size has been estimated to about 5.3 Gb, with the full genome being composed of 2n = 2x = 14 chromosomes (IBGSC, 2012). Genetic evidence suggests that barley underwent multiple domestication events (Morrell and Clegg, 2007;Dai, et al, 2012;Ren, et al, 2013;Wang, et al, 2016), or possibly was formed from a mosaic of wild progenitors from a wide geographic region (Poets, et al, 2015). One of the geographic origins for domesticated barley was located in the Near East where domestication is estimated to have occurred some 10,000 years ago (Zohary, et al, 2012).…”
Section: Barleymentioning
confidence: 99%
“…One of the geographic origins for domesticated barley was located in the Near East where domestication is estimated to have occurred some 10,000 years ago (Zohary, et al, 2012). Another region of importance to barley domestication was located on the Tibetan Plateau (Dai, et al, 2012;Ren, et al, 2013;Wang, et al, 2016).…”
Section: Barleymentioning
confidence: 99%